PERENCANAAN STRUKTUR ATAS SHELTER GENSET DESA TANJUNG, KECAMATAN TEBING TINGGI BARAT, KABUPATEN KEPULAUAN MERANTI - Septiadi, Ari; Bastian, Elfiani; Putra, Yorizal (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
MSTB-01 is part of the discovery spread in the eastern region of the Malacca Strait, which is in the inland onshore area in the Ringgit area and the surface conditions are marshy. The purpose of planning the ginset shelter is to help reduce the level of noise and noise pollution that can disturb the environment and also in an effort to assist the MSTB field development program. Data processing method using Staad Pro and manual calculation. The main column design uses steel profile H 350 x 175 x 7 x 11, column grating design uses steel profile C 125 x 65 x 6, main beam design uses steel profile H 200 x 100 x 5.5 x 8, beam rafter design uses steel profile H 200 x 200 x 8 x 12, The design of the beam foundation uses H 400 x 200 x 9 x 12 steel profiles, the design of the reinforcement / frame uses 2L 45 x 45 x 4 steel profiles, and the planning of the H 350 x 175 x 7 x 11 column connection with the base plate uses bolts with a plan diameter of 30 mm and a plate thickness of 20 mm, and a weld foot thickness of 3.5 cm and anchor length of 550 mm. Keywords: MSTB, Shelter, Staad ProV22, Steel Profile